Comparative Analysis of the Financial Performance of Pt Mayora Indah Tbk (Myor) and Pt Indofood Cbp Sukses Makmur Tbk (Icbp) Based on Profitability and Solvency Ratios for the 2021–2024 Period. - Rama Gustiawan; Hasan Basri; Ratih, Susiana Dewi (Universitas Mohammad Husni Thamrin, 2026)
Economic decision-making is generally based on an analysis of the financial performance of companies listed on the Indonesia Stock Exchange, including those in the food and beverage sector. Financial performance is assessed using standard financial ratios. The national economy underwent changes in 2021 during the COVID19 pandemic, then gradually improved in 2022. This picture of the national economy is reflected in the financial performance of companies listed on the Indonesia Stock Exchange. This study aims to analyze the comparison of the financial performance of PT Mayora Indah Tbk (MYOR) and PT Indofood CBP Sukses Makmur Tbk (ICBP) based on profitability and solvency ratios for the 2021–2024 period. The research method used is a quantitative descriptive approach with secondary data in the form of the companies' annual financial reports. The profitability ratios analyzed include Gross Profit Margin, Net Profit Margin, Operating Profit Margin, Return on Assets, and Return on Equity, while the solvency ratios consist of Debt to Asset Ratio and Debt to Equity Ratio. The results show that ICBP has superior and more stable profitability performance than MYOR, especially in terms of profit margin, while MYOR shows better performance in asset utilization efficiency and return on equity. In terms of solvency, both companies are in a healthy financial condition and meet industry standards, with MYOR having a lower level of financial risk. The recommendation from this study is for companies to continue to improve the efficiency of financial management in accordance with their respective characteristics, and for investors to consider their investment objectives when choosing a company.